Targeted Temperature Management after Intracerebral Hemorrhage (TTM-ICH): Methodology of a Prospective Randomized Clinical Trial. Issue 5 (July 2014) - Rincon, Fred; Friedman, David P.; Bell, Rodney; Mayer, Stephan A.; Bray, Paul F.
Rationale: Intracerebral hemorrhage causes 15% of strokes annually in the United States, and there is currently no effective therapy. Aims and hypothesis: This is a clinical trial designed to study the safety, feasibility, and efficacy of a protocol of targeted temperature management to moderate hypothermia in intracerebral hemorrhage patients. Methods: The targeted temperature management after intracerebral hemorrhage trial is a prospective, single-center, interventional, randomized, parallel, two-arm (1:1) phase-II clinical trial with blinded end-point ascertainment. Intracerebral hemorrhage patients will be randomized within 18 h of symptom onset to either 72 h of targeted temperature management to moderate hypothermia (32–34°C) followed by a controlled rewarming at of 0·05–0·1°C per hour or 72 h of targeted temperature management to normothermia (36–37°C) using endovascular or surface cooling. Outcomes: The primary outcome is the development of serious adverse events possibly and probably related to treatment. Secondary outcomes include in-hospital neurological deterioration between day 0–7, in-hospital mortality, functional outcome measured by the modified Rankin scale at discharge and 90 days, and effect of treatment allocation on cerebral edema and hematoma volume. Discussion: Intracerebral hemorrhage remains the most severe form of stroke with limited options to improve survival. As the early resuscitation phase in the intensive care unit represents the greatest opportunity for impact on clinical outcome, it also appears to be the most promising window of opportunity to demonstrate a benefit when investigating aggressive treatments. Conclusion: More research of novel therapies to improve outcomes after intracerebral hemorrhage is desperately needed. The results of the targeted temperature management after intracerebral hemorrhage clinical trial may provide additional information on the applicability of targeted temperature management after intracerebral hemorrhage.